Refusing to Die: Programmatic Goods in the Fight against COVID-19 in Sampang Regency - Hidayat, Endik; Susilo, Daniel (UI Scholars Hub, 2021)
This article discusses programmatic distributive politics in the villages in Sampang Regency during the COVID-19 pandemic. This study seeks to answer the forms of programmatic goods distributed in Sampang during the pandemic. This study employs qualitative methods and chose ten villages in Sampang as its case study due to Sampang’s achievement in maintaining its green zone status for the longest period in East Java. This article shows that there have been shifts in the bupati’s relationships with the village heads, from what was previously transactional prior to the pandemic to be more collaborative in efforts to contain the spread of the virus. This study also finds that the practice of distributive politics in Sampang during the pandemic fulfills the three criteria of programmatic politics: the accuracy of beneficiaries, transparency, and commitment to distribute goods without discrimination. The village heads in Sampang have acted as effective brokers in the implementation of village welfare programs, such as the installment of village volunteer posts against COVID-19, the free mask program for villagers, the BLT-Village Fund (BLT-DD) scheme targeting villagers from low-income households affected by the pandemic, the distribution of staple foods (sembako), the smart village program that provides free internet access in every village.